Influence of extraction methods using different solvents on caesalpinia pulcherrima leavaes - SHITAL S. PHUSE; DR. Z. H. KHAN; DR. Z. H. KHAN (International Journal of Pharma and Bio Sciences, 2017)
Plants synthesize many compounds that are critical to their existence. Plants have been a rich source of medicines. Hence, screening of plant extracts for the desired bioactivity is most important in medicinal plant research and extraction is the first step of the process. To achieve maximum possible extraction efficiency, it becomes necessary to optimize the extraction methodology. The need for selection of most appropriate extraction methodology is evidence from the fact that even different methods are applied on some plant material with some solvents, extraction efficiency can vary significantly. The aim of the current study was to show the influence of extraction methods on plant material. Magnetic stirrer and Soxhlet extraction had been done by using polar to non-polar solvents such as acetone and ethyl acetate continuously for 6 hrs and 4 hrs respectively. The analysis of Phytochemical encompasses phenols and flavonoids. The results were the mean values of the triplet readings. The presence of these phytochemical can be correlated with medicinal potential of this plant. In this present preview, an attempt has been made to give an overview of certain extractants and extraction processes with their advantages and disadvantages and it was concluded that Soxhlet extraction methods with polar solvent can be applicable as an efficient tool for the extraction of plant material from sample preparation and large scale industrial application.